ENHANCEMENT OF DISSOLUTION RATE OF MODAFINIL USING SOLID DISPERSIONS WITH POLYETHYLENEGLYCOLS - Vyas Jigar; Patel Jayvadan; Jain D. A. (Indonesian Journal of Pharmacy, 2012)
Solid  dispersions  (SDs)  of  modafinil  (MDF)  were  prepared using polyethyleneglycols (PEGs), in 1;1, 1;2 and 1;4 proportions by  fusion,  solvent  evaporation  and  physical  mixing  method. Differential  scanning  calorimetry  (DSC)  and  X-ray  powder diffractometry (XRD)  were  used to examine the physical state  of the  drug.  The  data  from  the  XRD  showed  that  the  drug  was converted  to  amorphous  form  as  the  number  and  intensity  of peaks  were  decreased  in  solid  dispersion  as  compared  to  pure drug and physical mixture of drug and carrier. DSC thermograms also  confirmed  the  change  in  physical  state  of  the  drug  as  the peaks were altered or disappeared. With the  highest  ratio of the carriers (1:4), the drug  solubility was enhanced by 38.68, 34.78 and 9.29 folds in solvent evaporation, fusion and physical mixing methods  respectively.  Solid  dispersion  batch  S6  containing drug:PEG6000  in  1:4,  was  selected  to  be  formulated  as  tablet (batch  TS6)  and  evaluated  for in  vitro drug  dissolution  &  six month  stability.  An  increased  dissolution  rate  of  modafinil  was observed  from  SDs  and  PMs,  as  compared  to  pure  crystalline drug.  The  dissolution  rate  of  modafinil  from  its  PMs  or  SDs increased with an increasing amount of polymer.Key  words:  Fusion,  solvent  evaporation,  physical  mixture,  in  vitro dissolution, characterization.